2016
DOI: 10.1007/s11136-016-1380-9
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of younger patients concerning activities after knee arthroplasty: are we asking the right questions?

Abstract: PurposeIndications for total and unicondylar knee arthroplasty (KA) have expanded to younger patients, in which Patient-Reported Outcome Measures (PROMs) often show ceiling effects. This might be due to higher expectations. Our aims were to explore expectations of younger patients concerning activities in daily life, work and leisure time after KA and to assess to what extent PROMs meet and evaluate these activities of importance.MethodsFocus groups were performed among osteoarthritis (OA) patients <65 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 63 publications
3
72
1
1
Order By: Relevance
“…Previous studies have noted that younger patients (<65 years) tend to have lower levels of satisfaction, despite excellent PROMs scores, up to 1 year following TKA [28,29]. Witjes et al [30] identified that younger patients tended to have expectations to perform multiple activities better following TKA, and that no commonly utilized PROM scoring systems adequately covered all that were considered important. The OKS may under-estimate the significance of certain activities to young patients and therefore over-state the quality of outcome achieved via a ceiling effect.…”
Section: Percentage Of Pa Ents Sta Ng This Expecta On Was Important Pmentioning
confidence: 99%
“…Previous studies have noted that younger patients (<65 years) tend to have lower levels of satisfaction, despite excellent PROMs scores, up to 1 year following TKA [28,29]. Witjes et al [30] identified that younger patients tended to have expectations to perform multiple activities better following TKA, and that no commonly utilized PROM scoring systems adequately covered all that were considered important. The OKS may under-estimate the significance of certain activities to young patients and therefore over-state the quality of outcome achieved via a ceiling effect.…”
Section: Percentage Of Pa Ents Sta Ng This Expecta On Was Important Pmentioning
confidence: 99%
“…Consequently, increased patient expectations and improved outcomes have been reported [5]. Therefore, instruments which seek to measure outcomes after TKA must adapt to meet the changing expectations [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…TKA does allow carrying out some knee-burdensome work activities, but a considerable percentage of TKA patients reported impaired ability to work and that they were dissatisfied with their level of ability to work. This is important as active work participation is an important factor in enhancing patients' quality of life and it gives structure to day-to-day life [47].…”
Section: Introductionmentioning
confidence: 99%